Relationship between warranty costs and defective cells. Case study of Xyratex (Malaysia) Sdn. Bhd. / Hassad Hassan (Faculty of Business Management, 2007)
The problem statement of this study is to find out the relationship of warranty costs towards the returned number of defective cells. Warranty cost will be determined by age, usage, cost of product and total repair cost. Through this research I will established the relationship of all of these variables with the number of defective parts returned. The research objectives are to determine the relationship between warranty costs and defective cells. The warranty costs are determined by the age, usage, product cost and total repair cost. This research is using secondary data as a major source of information. The data is obtained from Xyratex (Mal) Sdn. Bhd. and runs through August 2005 till November 2006. The methods used are simple regression analysis and Pearson-product-moment correlation coefficient to examine the relationship between cost and the number of returned defective parts (Cell and CPC2 cards). The finding of this research is to find out how the variables will give an impact to the warranty costs. Also, it is done to see which of the variables cost more that other variables. Therefore Xyratex (Mal) can make decision and focuses on the problematic parts